Please answer asap!
the recursive rule for a geometric sequence is given. a1=2 an=1/3an−1 enter the explicit rule for this sequence.

Respuesta :

ANSWER

The explicit rule is:

[tex]a_n=2{( \frac{1}{3} )}^{n - 1} [/tex]

EXPLANATION

The recursive rule is

[tex]a_1=2[/tex]

and

[tex]a_n= \frac{1}{3} a_ {n - 1}[/tex]

We can rewrite to get,

[tex] \frac{a_n}{a_ {n - 1}} = \frac{1}{3} [/tex]

This implies that, the constant ratio is:

[tex]r = \frac{1}{3} [/tex]

The explicit rule is given by:

[tex]a_n=a_1 {r}^{n - 1} [/tex]

We substitute the values to obtain, the explicit rule as:

[tex]a_n=2{( \frac{1}{3} )}^{n - 1} [/tex]